Trends in Enzyme Production from Citrus By-Products - Lima, Caio A. [UNESP]; Contato, Alex G.; de Oliveira, Fernanda; da Silva, Silvio S.; Hidalgo, Vitor B.; Irfan, Muhammad; Gambarato, Bruno C.; Carvalho, Ana K. F.; Bento, Heitor B. S. [UNESP] (MDPI, 2025)
Citrus fruit production generates substantial by-products, primarily from juice processing, which represent significant environmental and economic challenges. However, these residues, rich in polysaccharides, flavonoids, essential oils, and enzymes, offer an untapped resource for biotechnological applications. This review explores the potential of citrus by-products as substrates for enzyme production, focusing on key industrial enzymes such as cellulases, pectinases, xylanases, ligninases, lipases, and proteases. Various microbial strains have demonstrated the ability to convert citrus residues into high-value enzymes through solid-state and submerged fermentation. The optimization of fermentation conditions—including temperature, pH, moisture content, and the carbon-to-nitrogen ratio—further enhances enzymatic yields. The valorization of citrus waste aligns with circular economy principles, reducing environmental impacts while supporting sustainable bioproduct development for the food, biofuel, pharmaceutical, and textile industries. Future research should focus on scaling up enzyme production using citrus waste to improve economic feasibility and advance industrial biorefineries.
Keywords: agroindustry by-products; biorefinery; citric fruits; waste valorization